2014
DOI: 10.1074/jbc.m113.510388
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Myosin II-interacting Guanine Nucleotide Exchange Factor (MyoGEF) at Threonine 544 by Aurora B Kinase Promotes the Binding of Polo-like Kinase 1 to MyoGEF

Abstract: Background: Aurora B kinase (aurora B) and polo-like kinase 1 (Plk1) are critical regulators of cytokinesis. Results: Phosphorylation of MyoGEF at Thr-544 by aurora B promotes the binding of Plk1 to MyoGEF. Conclusion: Phosphorylation of MyoGEF by aurora B creates a docking site for Plk1. Significance: Coordinated regulation of MyoGEF localization and activation by aurora B and Plk1 contributes to the regulation of cytokinesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 60 publications
2
10
0
Order By: Relevance
“…Aurora B and Plk1 are two mitotic kinases that play critical roles in the regulation of cytokinesis (27,28). Aurora B and Plk1 can promote MyoGEF activation and localization at the central spindle during cytokinesis by phosphorylating Myo-GEF at Thr-544 and Thr-574, respectively (31,32). Our findings in this study show that phosphorylation of the MyoGEF carboxyl-terminal region by aurora B relieves the intramolecular interaction between the DH domain and the carboxyl-terminal region of MyoGEF (Figs.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…Aurora B and Plk1 are two mitotic kinases that play critical roles in the regulation of cytokinesis (27,28). Aurora B and Plk1 can promote MyoGEF activation and localization at the central spindle during cytokinesis by phosphorylating Myo-GEF at Thr-544 and Thr-574, respectively (31,32). Our findings in this study show that phosphorylation of the MyoGEF carboxyl-terminal region by aurora B relieves the intramolecular interaction between the DH domain and the carboxyl-terminal region of MyoGEF (Figs.…”
Section: Discussionsupporting
confidence: 57%
“…Depletion of Myo-GEF decreases RhoA/RhoC activation and suppresses breast cancer cell invasion (15). We also found that phosphorylation of MyoGEF at Thr-544 by aurora B creates a docking site for Plk1, thus leading to the binding of Plk1 to MyoGEF (31). In turn, Plk1 phosphorylates MyoGEF at Thr-574 (32).…”
Section: We Have Reported Previously That Nonmuscle Myosin Ii-interacmentioning
confidence: 76%
See 3 more Smart Citations